Physical function of COVID-19 survivors one year after intensive care discharge: Descriptive Cohort Study - Þóra Kristín Bergsdóttir 1996- (2022)
Background: Impairment in physical recovery and persisting symptoms have been found for COVID-19 survivors after intensive care unit (ICU) discharge. Understanding the recovery of COVID-19 survivors after discharge from the ICU is crucial for making future rehabilitative decisions. In addition, ICU stay is known to have substantial consequences including reduced physical health for years after ICU discharge. Objective: To evaluate the physical function and self-evaluation of health of patients admitted to the ICU with COVID-19 infection one year after ICU discharge. Second, to describe persisting symptoms, and third, to answer whether demographic or clinical variables correlate with one-year outcomes. Methods: Twenty-six COVID-19 survivors that were discharged from ICUs in Iceland in 2020 participated in this study, one year after their discharge. Physical function was measured with the six-minute walk test (6MWT) and the Physical Component Score of the Short-Form 36 Health Survey version 2 (SF-36v2 PCS). Patients self-evaluated health compared to their health before COVID-19 infection and persisting symptoms were both measured with a questionnaire. Demographic and clinical variables were gathered from a questionnaire and medical records. Descriptive analysis was performed and Spearman correlation coefficients were calculated for all variables. Results: The SF-36v2 PCS had a median of 46.1 points and 6MWT had a median of 520 meters. Seventy-seven percent of participants evaluated their health as somewhat worse or much worse one year after ICU when compared to before COVID-19 infection and the most common symptoms reported were fatigue and reduced exercise tolerance, 69.2% and 50.0%, respectively. Higher age (p-value 0.006), higher functional comorbidity index (p-value 0.025) and a higher number of persisting symptoms (p-value 0.005) correlated with shorter distance covered in the 6MWT. Conclusions: One year after ICU discharge, COVID-19 survivors’ physical function was lower than norm-based values. The majority ...